Rf and microwave radiation safety handbook. - Kitchen, Ronald
The leading professional guide to RF and microwave safety issuesA practical handbook for all involved in electronic design and safety assessment, RF and Microwave Radiation Safety covers the problems of RF safety management, including the use of measuring instruments and methods, radiation hazards and risks resulting from electromagnetic interference, as well as reviewing current safety standards and the implications for RF design. The second edition takes into account a wide range of technical and legislative changes, and has been revised in line with the latest EU and international standards.